2017
DOI: 10.5414/cn108992
|View full text |Cite
|
Sign up to set email alerts
|

Altered basophil function in patients with chronic kidney disease on hemodialysis

Abstract: Together, these data demonstrate that basophil functions related to adhesion and degranulation are altered in CKD patients on hemodialysis, which indicates a potential role for the basophil in the pathogenesis of complications related to infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 124 publications
(141 reference statements)
0
14
0
Order By: Relevance
“…24 CD62L is of interest for its role in basophil adhesion and its unique stable expression on basophils. 13 Indeed, cross-linking of CD203c and that of the adhesion molecules CD62L, CD11b and CD49d show a significant basophil activation judged by %CD63 expression. These experiments were performed at different temperatures (4°o r RT) to investigate the possibility of a temperature-dependent effect.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…24 CD62L is of interest for its role in basophil adhesion and its unique stable expression on basophils. 13 Indeed, cross-linking of CD203c and that of the adhesion molecules CD62L, CD11b and CD49d show a significant basophil activation judged by %CD63 expression. These experiments were performed at different temperatures (4°o r RT) to investigate the possibility of a temperature-dependent effect.…”
Section: Discussionmentioning
confidence: 97%
“…CD62L has been found to be quite stable on the basophil surface regardless of stimuli. 13 The observation that IL-33 has a more pronounced effect on CD62L shedding than IL-3 and fMLP is of special interest as IL-33 is secreted by endothelial cells 16 and mast cells 25 and is involved in the recruitment of basophils into the inflammatory foci. Considering that IL-33 is mainly found in tissues, we speculate that IL-33-dependent CD62L shedding is more likely to occur at extravascular sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L-selectin (CD62L) and very late antigen 4 (VLA-4, CD49d/CD29) are involved during basophil tethering and rolling on the endothelium. CD62L is a selectin that is not downregulated on basophils in the same way as it is on neutrophils upon activation [60]. The CD62L shedding on leukocytes is regulated by the cytoplasmic tail but also by mechanical shedding during rolling [61].…”
Section: Adhesion Moleculesmentioning
confidence: 99%
“…IL-33 induced CD62L shedding might tune the CD62L binding to ligands in tissue, such as proteoglycans [61]. It has been reported that CD62L is quite stable on basophils upon stimulation via several pathways such as TLR2, TLR4 and fMLP but that anti-FcεRI activation significantly downregulates CD62L [60]. Anaphylactic degranulation of basophils instantly releases histamine and cytokines such as IL-4 as well as expresses CD63 on the cell surface in response to activation.…”
Section: Adhesion Molecule Crosslinking and Cytokine Exposure Modulatmentioning
confidence: 99%